(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2015)
This work is focused on studying thermal pretreatment and leaching of copper and tin from printed circuit boards (PCBs) from used consumer equipment. Thermal treatment experiments were realized with and without presence of oxygen at 300 °C, 500 °C, 700 °C and 900 °C for 30 minutes. Leaching experiments were performed at 80 °C in 2M HCl in two stages. The first stage consisted of classic leaching experiments of samples without and after thermal treatment. The second stage consisted of oxidative leaching experiments (blowing of air or oxygen) with the aim to intensify metals leaching. The results of thermal treatment experiments show that maximal mass loss after burning (combustion) was 53 % (700 °C) and after pyrolysis 47 % (900 %). Oxidative leaching resulted in complete dissolution of copper and tin after 60. or 90 minutes of thermally treated samples. Pyrolysis and combustion have positive effects on metals dissolution in comparison with samples without thermal pretreatment. Moreover, the dissolution of metals is more effective and needs shorter leaching time.